2016
DOI: 10.1515/hc-2016-0103
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of copper complexes with chiral 1,2,4-triazine-oxazoline ligands

Abstract: The crystal structure determination of oxazoline-1,2,4-triazine ligand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The bonds and angles in molecules 5a-5c are very similar to those observed in previously reported closely related structures bearing a six-membered azaheteroaromatic ring linked with the chiral oxazoline ring by an anilino unit (Karczmarzyk et al, 2011;Woliń ska et al, 2016). As in the above-mentioned structures, in all the investigated molecules, the linker secondary N11-amine group is planar, with the sum of the angles around the N atom being 360, 359.6, 360 and 358.9 for 5a, 5b(A), 5b(B) and 5c, respectively, with an unusually large C2-N11-C12 angle of 131.6 (4) in 5a, 131.6 (3) in 5b(A), 131.5 (3) in 5b(B) and 131.9 (4) in 5c.…”
Section: Structure Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…The bonds and angles in molecules 5a-5c are very similar to those observed in previously reported closely related structures bearing a six-membered azaheteroaromatic ring linked with the chiral oxazoline ring by an anilino unit (Karczmarzyk et al, 2011;Woliń ska et al, 2016). As in the above-mentioned structures, in all the investigated molecules, the linker secondary N11-amine group is planar, with the sum of the angles around the N atom being 360, 359.6, 360 and 358.9 for 5a, 5b(A), 5b(B) and 5c, respectively, with an unusually large C2-N11-C12 angle of 131.6 (4) in 5a, 131.6 (3) in 5b(A), 131.5 (3) in 5b(B) and 131.9 (4) in 5c.…”
Section: Structure Analysissupporting
confidence: 84%
“…During our research, we developed ligands bearing a 1,2,4-triazine or pyridine ring linked with the chiral oxazoline by an anilino unit. The enantiocontrolling activity of the ligands was evaluated in the asymmetric nitroaldol reaction of nitromethane with a variety of aromatic and aliphatic aldehydes catalysed by copper ions (Woliń ska, 2013(Woliń ska, , 2014a(Woliń ska, ,b, 2016Woliń ska et al, 2016). This study revealed that the ligands with a 1,2,4-triazine ring exhibit a significantly higher enantio-inducing ability than the ligands possessing a pyridine ring due to the more electron-withdrawing character of the 1,2,4-triazine ring, which increases the positive charge of the copper cation centre and the electrophilicity of the aldehyde coordinating to the metal (Woliń ska et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…210, 254, and 309 nm. The first two bands (210 and 254 nm) are due to the maleamato ligand, and the band at 309 is associated with the metal to ligand charge transfer (MLCT) which is usually observed in copper complexes [56].…”
Section: Resultsmentioning
confidence: 99%
“…Chiral 3-oxazoline pyridine N-oxides substituted by with 1,2,4-triazine ring (50, 51) [68] were also examined in nitroaldol reaction of m-nitrobenzaldehyde but all attempts resulted in racemic nitroalcohol. An external base addition was tried and some improvement has been observed [69]. However, enantioselectivity grows (from racemate to 41% ee) only for bases with low pKa value.…”
Section: Chiral Heteroaromatic N-oxides As Ligands For Metal Catalysismentioning
confidence: 99%